Peningkatan Hasil Belajar Kognitif Peserta Didik pada Pembelajaran IPAS dengan Media Flashcard di Kelas VA SDN 2 Setu Wetan - Yustiani, Kharisma Fitria; Wahyuningsih, Asih; Fauziyah, Nita (Lembaga Yasin AlSys, 2025)
This research is motivated by a gap between learning objectives and student learning outcomes based on initial assessment results of IPAS learning in class VB at SDN 2 Setu Wetan, which is caused by the misalignment of teaching methods with students' learning styles. The purpose of this study is to describe the application of flashcard media in IPAS learning through a differentiated learning approach and to improve students' cognitive learning outcomes on the topic of